Design and constructability of funicular arched steel truss (FAST) false-work - El Sayed, Ahmed (AUC Knowledge Fountain, 2017)
The commercially available systems currently used in construction require high initial cost, take time to be erected and reduce the space in the construction site for the movement of material, equipment and labor as they prevent movement underneath them. The FAST system depends on developing a new false-work system depending on the concept of the funicular arch. It decreases the cost of the false-work as it uses less material and therefore needs lower initial cost than the commercially available systems. Further, the new system is environmentally friendly as it achieves a range between 45% and 50% saving in the amount of CO2 emitted to air due to the use of less material. The savings in the material used in the FAST system ranges between 45% to 51% depending on the covered area and it also provides more space in the construction site for the materials, equipment and workers to move underneath the system. The system also decreases the time needed for erection by range between 67% and 80% depending on the area and consequently helps in saving time and cost. To prove all of these advantages, experimental work is conducted on full scale models to study the mechanical and structural properties of the system.